MODERN BALLET'S BREAKTHROUGH AND RESHAPING OF TRADITIONAL BALLET AESTHETIC CONCEPTS - XinYi, Song (E-Journal VFU, 2025)
This paper delves into how modern ballet has broken through and reshaped traditional ballet aesthetic concepts. Research shows that modern ballet has fundamentally broken through the aesthetic norms of classical ballet by reconstructing body aesthetics, innovating creative paradigms, expanding artistic techniques, and transforming its cultural positioning. Modern ballet no longer pursues the aesthetic ideal of "openness, tension, straightness, and uprightness," but embraces diverse, natural, and even imperfect bodily expressions; it breaks away from linear narrative structures, adopts abstract and fragmented modes of expression, and actively integrates other art forms and modern technology; technically, modern ballet introduces floor work and improvisational elements, enriching its expressive means; culturally, modern ballet has shifted from elite art to social participation, actively responding to contemporary issues and developing localized expressions. While breaking through tradition, modern ballet has also expanded the boundaries of ballet art, enabling it to maintain its vitality and creativity in the contemporary cultural environment.
Keywords: Modern ballet; Classical ballet; Aesthetic concepts; Body aesthetics; Choreographic paradigm